2004
DOI: 10.1111/j.1601-5223.2001.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships among Portuguese Rye Based on Isozyme, RAPD and ISSR Markers

Abstract: The phylogenetic relationships of 10 rye landraces and cultivars from the north of Portugal and from Brazil were analysed using 20 isozyme loci, and a total of 511 PCR markers (342 ISSRs and 169 RAPDs). The isozymes were analysed in at least 100 plants of each population/cultivar and, therefore, we have data about intra and inter population/cultivar genetic variability. However, the analyses with ISSRs and RAPDs were obtained using a mix of 25 plants of each population. Therefore, each population/cultivar was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 18 publications
6
48
0
Order By: Relevance
“…Molecular data have shown more effectiveness than the morphological and physiological data. Matos et al (2001) and Fernández et al (2002) concluded that for genetic relationships studies, RAPD and ISSR markers were more useful than isozymes. Two RAPD and nine ISSR primers generated more than 80% of polymorphism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular data have shown more effectiveness than the morphological and physiological data. Matos et al (2001) and Fernández et al (2002) concluded that for genetic relationships studies, RAPD and ISSR markers were more useful than isozymes. Two RAPD and nine ISSR primers generated more than 80% of polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…RAPD and ISSR reactions were performed with minor modifications as described by Matos et al (2001). These reactions were carried out in 25 and 20 μL volume, respectively using T-Professional Thermocycler (Biometra, Göt-tingen, Germany).…”
Section: Rapd and Issr Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Isozymes and DNA-based markers are frequently used as molecular markers for taxonomic and systematic analyses of plants Bessega et al, 2000;Garkava et al, 2000;Matos et al, 2001;Ochiai et al, 2001). Many researchers Matos et al, 2001;Ochiai et al, 2001) have pointed out that DNA-based markers, such as random amplified polymorphic DNA (RAPD), were superior to isozymes in detecting genetic diversity. The isozymes represents allelic expression of the same locus, but fragments produced by RAPD are independent genetic markers (Ochiai et al, 2001) with a lower proportion of non-neutral markers than the former .…”
mentioning
confidence: 99%
“…PCR amplifications were performed in a final volume of 20 µl containing 2 μl of DNA template (~20 ng), 2 μl of Taq buffer with (NH 4 ) 2 SO 4 (10×), 1.6 μl of MgCl 2 (25 mM), 2 μl of ISSR primer (5 μM), 0.5 μl of dNTPs mix (10 mM each), 0.4 μl of Taq polymerase (5 U/μl) (Thermo Scientific, Waltham, USA). The amplification programme was described by Matos et al (2001). The PCR products were analysed on 1.7% agarose gels in 1× TBE running at 100 V for 210 min and stained in an ethidium bromide solution.…”
Section: Methodsmentioning
confidence: 99%